(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
This article offers a comprehensive overview of the existing literature in sport pedagogy on time-related studies. The research is organized and analyzed into four categories: how time is conceived, how time is measured, what is known about how time is used in physical education and sport contexts, and what is still unknown about time-related activities. In the part, a six point agenda for extending and continuing time research in sport pedagogy is proposed. Sport pedagogy is a branch of sport science concerned with educational processes including exercise, movement, play, and sport. Traditionally, structured physical education in schools has been emphasized with the aim of promoting children’s and teenagers’ growth and enabling them to engage in a range of sports and movement cultures. As a result, sport pedagogy and sport didactics are inextricably linked. There is no question that a serious, contributing science of sport pedagogy has only been present for a few years, regardless of how one defines it or whether one wishes to include or omit specific aspects of it.